2018
DOI: 10.1016/j.nicl.2018.03.021
|View full text |Cite
|
Sign up to set email alerts
|

The lost ability to distinguish between self and other voice following a brain lesion

Abstract: Mechanisms underlying the self/other distinction have been mainly investigated focusing on visual, tactile or proprioceptive cues, whereas very little is known about the contribution of acoustical information. Here the ability to distinguish between self and others' voice is investigated by using a neuropsychological approach. Right (RBD) and left brain damaged (LBD) patients and healthy controls were submitted to a voice discrimination and a voice recognition task. Stimuli were paired words/pseudowords pronou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 55 publications
(79 reference statements)
2
22
0
Order By: Relevance
“…Indeed, thought stimuli were designed to reflect thought content central to theories of cognitive vulnerability in depression 18 , 27 , 66 . The use of one’s voice was grounded in behavioral and phenomenological accounts of inner speech, cognitive neuroscience of own-voice perception and self-representations, and embodied cognition accounts of verbal thought 47 , 49 , 51 , 54 . Future research could, for example, be designed to dissociate internal attentional processing of self-referential thought content from motivationally-salient content or negative- from positive-valenced thought content, or between modes for audio delivery of simulated thought stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, thought stimuli were designed to reflect thought content central to theories of cognitive vulnerability in depression 18 , 27 , 66 . The use of one’s voice was grounded in behavioral and phenomenological accounts of inner speech, cognitive neuroscience of own-voice perception and self-representations, and embodied cognition accounts of verbal thought 47 , 49 , 51 , 54 . Future research could, for example, be designed to dissociate internal attentional processing of self-referential thought content from motivationally-salient content or negative- from positive-valenced thought content, or between modes for audio delivery of simulated thought stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Own-voice thought stimuli as a means to simulate verbal thought is grounded in work on behavioral and phenomenological accounts of inner speech 47 , 48 and cognitive neuroscience of own-voice perception and self-representations 49 , 50 . Hearing one’s own voice activates right prefrontal brain regions implicated in abstract self-representations and self-referential processes (not activated for example when hearing others’ voices) 49 , 51 , 52 nor when simply reading text 53 . Furthermore, our approach to simulated thought through one’s voice is also informed by embodied or simulated accounts of cognition 54 .…”
Section: Introductionmentioning
confidence: 99%
“…Neural mechanisms underlying the perception of self have been examined using faces 7,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] , as well as voices 18,[29][30][31] . These studies reported higher neural activities in subjects observing their own faces/voices than others' faces/voices.…”
Section: Neural Representations Of Own-voice In the Human Auditory Comentioning
confidence: 99%
“…The current study further supports lateralized findings by demonstrating that self/other discriminations are significantly different between the hemispheres. These data add to a growing amount of evidence that the RH appears critical in evaluating self/other differences, tested across a number of different modalities in non-patient [ 28 , 80 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ], and patient populations [ 35 , 105 , 106 , 107 , 108 , 109 ]. Decety and Lamm [ 110 ], have suggested that superior right parietal processing may be critical for both switching and differentiating self/other distinctions.…”
Section: Discussionmentioning
confidence: 79%